Enhancing Financial Statement Quality: The Moderating Role Of Coercive Pressure In Government Entities - Cahyo Dwi Mulyantoro; Nurkholis Nurkholis; Sari Atmini (Universitas Muhammadiyah Malang, 2024)
Purpose: This study aims to examine the effect of human resource competence, accounting information system quality, and internal control systems on the financial statement quality of central government accounting entities, with coercive pressure as a moderating variable. Methodology/approach: Primary data was collected from 118 central government work units through questionnaire distribution. The data was analyzed using the Partial Least Square (PLS) statistical technique to examine the relationships between variables. Findings: Human resource competence, accounting information system quality, and internal control systems are proven to be factors that can affect financial statement quality. Coercive pressure can strengthen the effect of accounting information system quality on financial statement quality, but it cannot strengthen or weaken the effect of human resource competence and internal control systems. Practical implications: Enhancing the competence of financial statement preparers, utilizing accounting information systems, and implementing effective internal control systems should be encouraged to improve the quality of central government financial statements. Coercive pressure must be responded to properly by utilizing the advantages of accounting information systems. Originality/value: The examination of coercive pressure in moderating the factors affecting the financial statement quality is the novelty of this study.